Benign Childhood Occipital Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The clinical and EEG features of the syndrome of benign childhood occipital epilepsy (Panayiotopoulos syndrome [PS]) were studied in 66 patients seen between 1990 and 1997 at the Hospital Nacional de Pediatria "Juan P Garrahan," Buenos Aires, Argentina.